A new species of Miconia (Miconieae, Melastomataceae) from Northwest Ecuador - Palacios, Walter A.; Fernández-Fernández, Diana M.; Michelangeli, Fabián A. (Phytotaxa, 2018)
A new species, Miconia yeseniae, is described and illustrated. The species is part of the Amblyarrhena section and is distinguished from others of the genus by the large (2–2.5 cm long) pink petals, the well-developed outer calyx teeth (4.9–5.1 mm long) and the 10-angular ovary. The most related species are Miconia glandulistyla, M. floribunda, M. codonostigma, M. glandulistyla and M. grandiflora. The new species reaches 8 m in height and is known only from the type locality, on the slopes of Cerro Golondrinas, on the Andean flanks of the northwest of Ecuador, in the humid forest.